Soluble Endoglin Serum Level is Higher in Preeclampsia Compared to Molar and Normal Pregnancy - Puspitasari, Maya K. (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To analyze the differences of maternal serum soluble endoglin level in preeclampsia, molar pregnancy, and normal pregnancy, and to analyze the correlation between maternal serum soluble endoglin level with gestational age. Method: This is a cross-sectional comparative analytic study involving 18 preeclampsia cases, 18 molar pregnancies, and 18 normal pregnancies. The sample were obtained from Dr. Hasan Sadikin hospital and six satellite hospitals from January until March 2013. The comparison of mean seng serum level of the preeclampsia, molar pregnancy, and normal pregnancy group was calculated using Kruskal Wallis, and the correlation were calculated using Rank Spearman. Result: The mean level of seng serum in preeclampsia group was higher (168.79 ng/ml) than in molar pregnancy (43.47 ng/ml) and normal pregnancy (32.38 ng/ml). There is no significant difference of serum seng level between molar and normal pregnancy, with p value of 0.393 (p>0.05). There is significant differences of seng serum level between preeclampsia group and molar pregnancy (p=0.000), but no significant differences between molar and normal pregnancy, p value=0.393 (p>0.05). There is positive correlation between seng serum level of normal pregnancy with gestational age (rs=0.647; p